2021
DOI: 10.3389/fendo.2021.691557
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Altered ATRX/DAXX Gene in Pancreatic Neuroendocrine Tumors: A Meta-Analysis

Abstract: BackgroundPancreatic neuroendocrine tumors (PanNETs) are a heterogeneous group of neoplasms with increasing incidence and unpredictable behavior. Whole-exome sequencing recently has shown very frequent somatic mutations in the alpha-thalassemia/mental retardation X-linked (ATRX) and death domain-associated protein (DAXX) genes in PanNETs. And the prognostic significance of altered ATRX/DAXX genes in PanNETs patients have been revealed in several reports. However, many of these include small sample size and hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…If the expression of ATRX and DAXX is retained, then the prognosis of patients with pancreatic neuroendocrine tumours is improved ( 18 , 19 ). This study is the first to address the expression of these two markers in patients with SPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the expression of ATRX and DAXX is retained, then the prognosis of patients with pancreatic neuroendocrine tumours is improved ( 18 , 19 ). This study is the first to address the expression of these two markers in patients with SPC.…”
Section: Discussionmentioning
confidence: 99%
“…The genes for α-thalassemia/mental retardation syndrome X-linked protein ( ATRX ) and death domain-associated protein ( DAXX ) play important roles in chromatin remodelling at the telomeres and other genomic sites in normal tissues; moreover, whole-exome analysis has revealed that inactivated somatic mutations of these genes are frequently observed in pancreatic neuroendocrine tumours ( 17 ). Subsequent studies have revealed that loss of ATRX and DAXX is associated with chromosomal instability and a shorter survival period in patients with pancreatic neuroendocrine tumours ( 18 , 19 ). However, the frequency of loss of ATRX and DAXX expression and its prognostic significance in SPC patients has not yet been analysed.…”
Section: Introductionmentioning
confidence: 99%
“…There is also more clinical value of the finding of ATRX and DAXX gene mutations. In one recent meta-analysis, altered ATRX and DAXX gene had significant correlation with the prognosis of pancreatic NET ( 15 ). Disease- and relapse-free survival significantly decreased in patients who had ATRX and DAXX mutations ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…A loss of DAXX/ATRX is associated with chromosome instability and reduced survival [27]. Recently, a meta-analysis of 14 studies with a total of 2313 patients has supported the prognostic significance of altered DAXX/ATRX genes in pNETs with a combined HR of 5.05 for disease-free survival (95% CI: 1.58-16.20, p = 0.01) [30,31]. In metastatic disease, DAXX/ATRX loss seems to be associated with longer survival.…”
Section: Prognostic Factors In Metastatic Pancreatic Netmentioning
confidence: 99%